(untitled) (AACINI - International Journal of Industrial Engineering, 2021)
The presentation reflects on the certification of technical knowledge in the framework of an investigation of Labor Trajectories and Certification of Trades, at the National Technological University - Delta Regional College (UTN-FRD), in the period 2003-2015. To do this, it will focus on the reconstruction of the labor trajectories of people in the Zárate - Campana region who went through the device called "Trades certification program", in order to determine the impact that this program had on a population that certified as continuously. The device implemented in UTN FRD emerged in 2003, trying to respond to local demands in the face of the lack of people with trades, as a consequence of the deindustrialization of the times that preceded it. These conditions were repeated, in a similar way, since 2016 with changes in the economic model. These conditions mentioned, among others, that impact the world of work are: a marked contraction of the market that is evident with a drop in the activity rate, high unemployment rate, precarious and informal employment, closing of SME industries, one of the growth engines of the national economy. The guiding question was to investigate the meanings and representations that people who certify their trade through the "Program" construct. Among the objectives, characterize both personal, family and peer perceptions and establish the qualifications that operate in the labor field on said certification. As sources of information, the general base of enrolled in the faculty program was used to carry out the clipping and sociodemographic characterization of the sample and semi-structured interviews, using a mixed methodology.